Evaluation of information needs of agricultural extension agents in Ghana. (November 2017) - Sam, Joel; Osei, Simon K.; Dzandu, Lucy P.; Atengble, Kirchuffs
The agricultural sector plays a decisive role in Ghana's economy, employment, and food security. The study set out to assess the information needs of agricultural extension agents across all the agro-ecological zones of Ghana, in order to provide them with the right information. A structured field survey methodology was used for the study and 472 agricultural extension agents from 40 districts in Ghana served as the respondents. The findings of the study revealed that agricultural extension agents regularly sourced for information from books and reports; visual or pictorial information was the most preferred format for package of information. The AEAs used agricultural extension information to assist in the discharge of their work, and as a basis for advice to farmers on general farm planning and consultancy among others. Challenges identified in accessing information included inadequate information infrastructure and training avenues. The AEAs suggested that critical information infrastructure such as libraries, information centers, and databases be provided as measures to offset the challenges. The study recommended that efforts should be directed at improving extension agents' access to information infrastructure and that different and wide-ranging media should be developed to supply information to the AEAs.